KESETARAAN GENDER DALAM RUKYATUL HILAL: MENINJAU KETERLIBATAN KESAKSIAN PEREMPUAN DALAM PENENTUAN AWAL BULAN (RAMADAN, SYAWAL DAN ZULHIJJAH) - Haq, Aisyah Maulidatul Haq; Hasan, Hamza; Shuhufi, Muhammad (UIN ALAUDDIN MAKASSAR, 2024)
This research is motivated by the testimony of men who are identical in rukayatul hilal compared to women. This research is library research using a normative approach. Primary data sources were obtained from documents such as books, articles, decisions of the Minister of Religion and sources related to gender and women's testimony in rukyatul hilal. The results of this research show that the testimony in rukyatul hilal reflects the spirit of gender equality, although the involvement of women in testimony determining the beginning of the month (Ramadan, Shawwal and Zulhijjah) is still very minimal, namely 3% with testimony starting from 1 Shawwal 1421 H/2000 AD to 10 Zulhijjah 1440 H/2019 AD.